Molecular phylogeny and biogeography of African diploid barbs, 'Barbus', and allies in Africa and Asia (Teleostei: Cypriniformes). (20th March 2016) - Ren, Qiu; Mayden, Richard L.
Abstract : African diploid barbs (' Barbus', Clypeobarbus, Barboides, etc.) are a group of small cyprinids with a body size less than 20 cm and widely distributed in drainages across Africa. These species constitute a significant component of African freshwater fish fauna. This study is the first to focus on the molecular systematics and biogeography of African diploid barbs ' Barbus' and its African and Asian allies using both mitochondrial and nuclear genes. We test for monophyly of groups, determine interspecific relationships and estimate the time of divergence of 52 species of ' Barbus' and allies using two mitochondrial and four nuclear genes. Resulting trees demonstrate that ' Barbus' and allies ( Systomus, Barboides, Clypeobarbus and African tetraploid barbs) form a strongly supported clade; however, ' Barbus' is not resolved as monophyletic. Divergence time analyses identify the separation between Systomus and ' Barbus' plus African allies may have occurred around 26 MYA. In addition to the phylogenetic results, these findings highlight the need for more thorough taxonomic and systematic studies on ' Barbus' and allies using morphological and additional molecular data and greater taxon sampling, including the type species of the genus Enteromius, ' Barbus' potamogalis .